ANALISIS PENDIDIKAN KARAKTER DISIPLIN PADA SISWA KELAS V SD - Fajar Riski Ramadhon; Anggit Grahito Wicaksono; Sarafuddin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
The purpose of this study was to determine: (1) the implementation of disciplinary character education, (2) supporting and inhibiting factors, and (3) its impact on fifth grade students. The research method used descriptive qualitative with a case study on five fifth grade students. Data were obtained through observation, interviews, and documentation, analyzed using an interactive model, and tested for validity through source triangulation. The results of the study showed that the implementation of disciplinary character education was carried out through habituation, teacher role models, and enforcement of rules, but was not optimal because some students only obeyed when supervised. Supporting factors included teacher role models, school rules, and parental support, while inhibiting factors included low student self-awareness, inconsistent family parenting patterns, and peer influence. The impact was seen in positive behavioral changes such as punctuality, compliance with rules, and seriousness in doing assignments, although not yet consistent. Also, disciplinary character education at SD Negeri 02 Jeruksawit has been running but is not evenly distributed, so it still requires cooperation between the school, parents, and the environment.